THE RELATIONSHIP BETWEEN SUBJECTIVE COMPLAINTS OF LOW BACK PAIN AND SLEEP QUALITY - Dinanti Bintang Shahrani; Tanti Ajoe Kesoema; Erna Setiawati; Rahmi Isma Asmara Putri (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Low back pain is a frequently occurring symptom closely associated with society, both in Indonesia and globally. It can be influenced by both unmodified and modified factors, such as excessive physical activity, obesity, body posture, and psychological factors. Considering these risk factors, it is known that individuals in the productive age range (<45 years) have a significant risk of experiencing low back pain. Objective: This study examines the correlation between low back pain subjective complaints and sleep quality in students at the Faculty of Medicine Diponegoro University. Methods: Analytical observational study with a cross-sectional design. Research subjects are students from the Faculty of Medicine, Diponegoro University, Semarang, which were selected using consecutive sampling. The low back pain subjective complaint is determined using the NRS and sleep quality data are determined by PSQI questionnaire. The relationship between the low back pain subjective complaint and sleep quality is analyzed using the Chi-Square correlation test and Fisher’s Exact alternative test. Results: From a total of 51 research subjects, the analysis of subjective low back pain complaint scores in relation to sleep quality yielded a p-value of 0.362. Therefore, it can be concluded that there is no significant relationship between subjective low back pain complaint scores and sleep quality. Conclusion: There is no relationship between the subjective complaints of low back pain and sleep quality among students at the Faculty of Medicine, Diponegoro University.